Does an osteotomy performed in congenital pseudarthrosis of the tibia accompanied by tibial angular deformity heal? - Yaoxi Liu; Gunaghui Zhu; Shijie Liao; Haibo Mei; Xiaofei Ding (Journal of Orthopaedic Surgery and Research)
Abstract Background The role of osteotomies in deformity correction in congenital pseudarthrosis of the tibia (CPT) remains controversial. This study aims to evaluate the efficacy of tibial closing osteotomy correction for tibial angular deformity in CPT patients. Methods This study selected CPT patients who underwent CPT combined with tibial closing osteotomy in our hospital from January 2011 to May 2022 as the research subjects. The inclusion criterion was children with Crawford IV CPT who also had angular deformities. The PACS system was used to measure the distance between the tibial osteotomy and the tibial pseudarthrosis, as well as the tibial angle. The degree of healing of tibial pseudarthrosis was evaluated via the RUST score. If the RUST score is greater than 8, tibial pseudarthrosis is considered to have achieved primary union. After surgery, X-rays were taken every 2 months until the patient’s tibial pseudarthrosis healed. Results Twenty-three patients with CPT underwent combined surgery and proximal tibial osteotomy. The average age at the time of surgery was 48.7 months (14–158 months). There were 15 males and 8 females, including 17 patients with type 1 neurofibromatosis. Nineteen patients had proximal tibial dysplasia. There were 12 cases on the left and 11 cases on the right. The average angle of the tibia in the preoperative anterior posterior position was 10.3°, and the average angle of the tibia in the preoperative lateral position was 20°. All patients achieved primary union, with an average union time of 4.7 months. The average distance between the osteotomy site and the tibial pseudarthrosis site was 6.5 cm. Twenty-two patients achieved union at the osteotomy site during the healing process of tibial pseudarthrosis. One patient did not achieve union at the osteotomy site, but healing was achieved after a wrapped autogenous iliac bone graft was applied for four months. Conclusion CPT patients with tibial angular deformities can undergo combined surgery and tibial closing osteotomy correction. It has little effect on the healing of the pseudarthrosis of the tibia, and tibial closing osteotomy may be safe and effective for correcting tibial angular deformity. The preliminary findings requiring further validation.